2017
DOI: 10.1016/j.exer.2017.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Meibocyte differentiation and renewal: Insights into novel mechanisms of meibomian gland dysfunction (MGD)

Abstract: This paper reviews our current understanding of age-related meibomian gland dysfunction (MGD) and the role of the nuclear receptor, peroxisome proliferator-activated receptor gamma (PPARγ), in the regulation of meibomian gland function, meibocyte differentiation and lipid synthesis. The studies suggest that PPARγ is a master regulator of meibocyte differentiation and function, whose expression and nuclear signaling coupled with meibocyte renewal is altered during aging, potentially leading to atrophy of the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 46 publications
(53 reference statements)
3
63
0
1
Order By: Relevance
“…13 Down regulation of PPARγ is thought to underlie the decreased meibocyte differentiation and lipid synthesis seen in aging, leading to gland atrophy and a hyposecretory state. 6,11 Interestingly, hyperkeratinization and gland obstruction were not found to play a role in the development of MGD in this mouse model. 6 …”
Section: Pathophysiology Of Mgdmentioning
confidence: 60%
See 2 more Smart Citations
“…13 Down regulation of PPARγ is thought to underlie the decreased meibocyte differentiation and lipid synthesis seen in aging, leading to gland atrophy and a hyposecretory state. 6,11 Interestingly, hyperkeratinization and gland obstruction were not found to play a role in the development of MGD in this mouse model. 6 …”
Section: Pathophysiology Of Mgdmentioning
confidence: 60%
“…3–5 Newer studies have added to this paradigm and describe meibocyte abnormalities as a contributing mechanism in MGD. 6,7 Support for the role of the meibocyte in MGD comes from pathophysiologic studies evaluating intrinsic (e.g. aging) and extrinsic (e.g.…”
Section: Pathophysiology Of Mgdmentioning
confidence: 99%
See 1 more Smart Citation
“…A different approach was undertaken by Jester and colleagues who tested the role of PPARγ in modulating the lipid metabolism in cultured mouse meibocytes and mice (Hwang et al, 2017; Jester et al, 2016). It was observed that the amount of lipid produced by the cells was dependent on the serum levels in the culture media: low serum concentrations (0% to 2%) led to a marked reduction in the lipid production, as evidenced by HCS LipidTox staining.…”
Section: A Concept Of Meibogenesismentioning
confidence: 99%
“…It was recently proposed that renewal of meibocyte could rely on a limited number of progenitor meibocytes, whereas meibomian gland duct would be derived from multiple origins. 49,50 This can explain why HMGECs induced CK expression in a pattern closely resembling that of ductal cells in response to an air-rich environment. Even if appropriate progenitor populations are found in HMGECs, they may have been exhausted because HMGECs were established from donors ranging from 35 to 85 years.…”
Section: Discussionmentioning
confidence: 95%